2009
DOI: 10.1111/j.1399-5448.2008.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Practical matters, rather than lack of trust, motivate non-participation in a long-term cohort trial

Abstract: Trust in researchers may be a necessary prerequisite in order for people to be willing to participate in research, but practical matters such as time that has to be spent or pain involved in collecting blood were more important factors than lack of trust in explaining opt out in relation to the ABIS study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…These finding are consistent with prior reports identifying similar reasons for why families fail to join longitudinal studies like TEDDY [8,9]. It appears that even when families join a longitudinal study, protocol issues including blood draws and extensive time demands remain important for study retention.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These finding are consistent with prior reports identifying similar reasons for why families fail to join longitudinal studies like TEDDY [8,9]. It appears that even when families join a longitudinal study, protocol issues including blood draws and extensive time demands remain important for study retention.…”
Section: Discussionsupporting
confidence: 82%
“…Having someone who is watching the child for the development of diabetes and getting the child's antibody results were two of the most important reasons for staying in the TEDDY study, findings reported previously [7]. It is also important not to underestimate participants' altruistic objectives for participating in research [8]. In a phase III clinical trial [4], in addition to possible personal benefit, respondents often mentioned the possibility of helping others.…”
Section: Discussionmentioning
confidence: 95%
“…The original consent was given at birth (1997–1999). At each clinical checkpoint, the parents were informed and given the opportunity to remain in or opt out 19. Information about the study’s aims was distributed to the families (sample at 1, 2.5, 5 and 8 years being the cohort who consented at birth; ie, 78.6% of the original birth cohort) by letters of information, brochures to the children (at 8 years) and through the ABIS website.…”
Section: The Abis Studymentioning
confidence: 99%
“…The All Babies in Southwest Sweden (ABIS) study, a longitudinal epidemiological study targeting children from birth, enrolled 78.6% of eligible participants and noted practical study characteristics such as participant time burden and blood sampling as the most common reasons for enrollment refusal. ABIS data also suggested interactions between participant characteristics (e.g., maternal age, parent education level) and reasons for enrollment refusal [4]. While these studies provide relevant information on enrollment experiences, there may be international differences in these experiences which are not captured by country-specific studies.…”
Section: Introductionmentioning
confidence: 99%